Workflow management systems -- a powerful means to integrate radiologic processes and application systems...Proccedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: Performance Improvement in Radiology.' Houston TX, May 6-9, 1999 - Schmidt J; Meetz K; Wendler T (Journal of Digital Imaging)
This presentation describes a research project investigating the suitability of model-based Workflow Management Systems (WfMS) to support radiological process. The following aspects are covered: process modeling, process enactment, and architecture of workflow-enabled application systems. Copyright (c) 1999 by W.B. Saunders Company